Effect of Pressure, Opportunity, Rationalizations, Capability and Arrogance in The Concept of The Fraud Pentagon - Neng Putriyanti; Ari Dewi Cahyati (JAFFA, 2020)
The purpose of this study was to determine whether the elements in the fraud pentagon concept could detect the potential for fraud in financial statements. The sample in this research is state-owned companies (BUMN) listed on the Indonesia Stock Exchange (BEI) in 2014-2018. The sampling method used was purposive sampling technique. The analytical tool in this research uses the logistic regression analysis method. The results showed that the variables pressure and rationalizations had a significant positive effect on fraudulent financial reporting. The opportunity variable has a significant negative effect on fraudulent financial reporting. Meanwhile, the pressure variable, opportunity variable, capability variable, and arrogance variable had a positive and insignificant effect on fraudulent financial statements.